Evaluation of an Electronic Consultation Service in Obstetrics and Gynecology in Ontario. Issue 6 (June 2016) - Shehata, Fady; Posner, Glenn; Afkham, Amir; Liddy, Clare; Keely, Erin
Abstract : OBJECTIVE: To describe the effectiveness of an electronic consultation (eConsult) service by examining the number of traditional referrals that were avoided as a result of the service, to characterize the type and content of the clinical questions being asked, and to describe the time required for the specialist to complete each eConsult. METHODS: This is a retrospective electronic chart review study. All eConsults directed to obstetrics and gynecology from July 2011 to January 2015 were reviewed. Each eConsult was categorized by clinical topic and question type in predetermined categories. Mandatory post-eConsult surveys for primary care providers were analyzed to determine the number of traditional consults avoided and to gain insight into the perceived value of eConsults. The amount of time reported by the specialist to answer each eConsult was analyzed. RESULTS: A total of 394 of 5, 597 eConsults were directed to obstetrics and gynecology (7.0%). In 34.3% of eConsults, primary care providers indicated that a traditional consult was avoided. Pregnancy issues and gynecologic cancer screening issues were the most common queries. Primary care providers highly valued the eConsult and the majority of eConsults were completed within 15 minutes (98.8%). CONCLUSION: Electronic consultations were effective at reducing the number of traditional consults requested over 3.5 years. This initiative has potential to reduce current wait times for traditional consultation in Canada and to make the consultation process more effective. The service was feasible and well-received by primary care providers. Abstract : An electronic consultation service in Ontario is effective in reducing the number of traditional consults requested by primary care providers and is well-received.